Chelation-controlled intermolecular alkene and alkyne hydroacylation: the utility of beta-thioacetal aldehydes. - Willis, M; Randell-Sly, H; Woodward, R; Currie, G (2005)
[reaction: see text]. Beta-thioacetal-substituted aldehydes, which are conveniently prepared from the corresponding ynals, can be combined with a range of alkynes or electron-poor alkenes to deliver intermolecular hydroacylation adducts. The reactions employ [Rh(dppe)]ClO4 as a catalyst and are proposed to proceed via a chelated rhodium acyl intermediate. The thioacetal-containing products can be deprotected to the corresponding ketones or reduced to alkanes in good yields.